Kata Pemeri: Satu Takrifan Nahuan dalam Kerangka Ayat Bahasa Melayu (Jurnal Bahasa, 2011)
The term copula verb was derived from Latin grammar via Dutch and English and has been applied by some scholars as adalah and ialah in Malay. Among these scholars, some have attempted to identify copula verbs in Malay - either in overt or covert form, i.e. in a grammatically independent form or in a form hidden in non-verbal words. These studies have taken the view that sentences in Malay conform to the framework of [subject NP + predicate verb]. Other scholars have treated the words adalah and ialah as "descriptives" or "descriptive particles" to describe the relationship between subject and predicate. This paper aims to examine what the distinctive characteristics and qualities of the two words are. In order to do so, attention is given to the functions of the "affirmatives" of adalah and the "adverbial conjunction" of ialah in affirmative sentences. The function of copula verbs in European languages will also be compared with these two words, and the effectiveness of the use of adalah and ialah within the framework of Malay sentences will be evaluated. The article concludes that the words adalah and ialah are not copula verbs. Instead, they assume the function of "assertion" or "analyticity" of a predication, i.e. the function of "description" as a whole. Hence, the term "descriptives" is found to be more appropriate for this particular word class.Keywords: inflection, copula verb, lexical verbs, positives, descriptives, grammatical agreement, descriptive particles, interrogative sentence marker